Exposure risks and ineffectiveness of total release foggers (TRFs) used for cockroach control in residential settings - DeVries, Zachary C. (BMC Public Health, 2019)
BACKGROUND: The German cockroach, Blattella germanica, is one of the most challenging pests to eradicate from indoor environments. Professional pest control is often prohibitively expensive, prompting low-income residents to turn to over-the-counter consumer products, including total release foggers (TRFs, “bug bombs”). Despite their widespread use, little is known regarding either the associated pesticide exposure risks or the efficacy of TRFs. METHODS: Cockroach-infested homes were recruited into the study. Wipe samples were collected from various surfaces before TRFs were discharged, immediately after, and one month later to determine pesticide exposure risks in 20 homes (divided equally among four different TRF products). Simultaneously, cockroach populations were monitored in all homes to assess the efficacy of TRFs. In parallel, 10 homes were treated with gel baits (divided equally between two bait products), to compare TRFs to a more targeted, low-risk, do-it-yourself intervention strategy. RESULTS: TRFs failed to reduce cockroach populations, whereas similarly priced gel baits caused significant declines in the cockroach populations. Use of TRFs resulted in significant pesticide deposits throughout the kitchen. Across all products, pesticides, and horizontal kitchen surfaces, pesticide residues following TRF discharge were 603-times (SEM ±184) higher than baseline, with a median increase of 85 times. CONCLUSIONS: The high risks of pesticide exposure associated with TRFs combined with their ineffectiveness in controlling German cockroach infestations call into question their utility in the marketplace, especially because similarly priced and much safer bait products are highly effective in the indoor environment.